Destruction : Documents of Contemporary Art. - Spieker, Sven; Badiou, A.; Berke, J.; Buck-Morss, Susan; Derrida, Jacques, 1930-2004; Foster, Hal; Polgovsky Ezcurra, Mara; Galende, Frederico; Gapin, Richard; Gamboni, Dario; Görner, Klaus; Kee, Joan; et al. (London : Whitechapel Gallery, 2017)
Ai Wei wei ; Altoray, Gabor ; Baldessari, John ; Chwatczyk, Jan ; Conner, Bruce ; Huang Yong Ping ; Pope L., William ; Song Dong, Bonvincini, Monika ; Brener, Alexander ; Brisley, Stuart ; Jezik, Enrique ; Meuhl, Otto ; de Saint Phalle, Niki ; Latham, John ; Gordon, Douglas ; Ono,Yoko ; Vostell, Wolf ; Raynaud, Jean-Pierre
vandalisme, destructie,kapitalisme, terrorisme
boek